The Repentant Bath of Abah Anom's Inabah: A Hydrotherapy for Drug Addicts in Muslim Society - Nurhamzah Cahyo Setio; Asep Harry Hernawan; Rusman Rusman; Chiedu Eseadi (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2023)
The repentant bath of Abah Anom's Inabah is hydrotherapy, and many parties admit its success in curing drug addicts. However, many parties have yet to understand bathing repentance in the concept and implementation process. This paper described the concept and implementation of the Abah Anom's Inabah. In addition, this article is also projected to explain the impact of the repentance bath on drug addict patients. This study used a qualitative descriptive research method with a phenomenological approach. The results of this research are conceptually the Abah Anom's Inabah as a form of internal and external hydrotherapy to heal drug addicts is based on the postulate of the Qur'an and hadith. Such as concerning water as the primary source of life for God's creatures, concerning bath as a way to purify both physical and mental conditions, the benefits of water in purifying physical and mental states, concerning water from the sky (rain) as a purifier and the prohibition of khamr (which is intoxicating). The implementation of the Abah Anom’s Inabah is like the janābah bath or the bath performed after having major ḥadaś by reading special intentions and prayers. It is carried out in the last third of the night every morning at around 02.00 am in stages: the preparation, the implementation, and the closing. Based on the data, it was concluded that Abah Anom's Inabah positively impacts patients through self-awareness, body cleanliness from toxins, and peace of soul.